Demography and pattern of care of patients with head-and-neck carcinoma: Experience from a tertiary care center in North India - Roy, Somnath; Mandal, Tanmoy; Das, Sudeep; Srinivas, Sujay; Agarwal, Anshul; Gupta, Anuj; Singh, Arpita; Singh, Anil; Kuraparthy, Samasivaiah; Kapoor, Akhil; Ghosh, Ranti; Mishra, B (Cancer Research, Statistics, and Treatment, 2020)
Background: Head-and-neck cancer (HNC) is one of the most common cancers in India and requires a multidisciplinary approach for disease management. Objectives: We aimed to report the demographic profile and pattern of care of patients with HNC and their treatment compliance at our center. Materials and Methods: This single-center, retrospective study was conducted in the Department of Medical Oncology of Homi Bhabha Cancer Hospital, Tata Memorial Center, Varanasi, India, from May 2018 to April 2020. Patients with HNCs of any sub-site, stage, and histology were included in the study. The patients underwent routine clinical and imaging evaluation, baseline investigations, and tissue biopsy. After diagnosis and staging, the cases were discussed by a multidisciplinary team for treatment planning. The number of patients presenting at our center within the specified time period, the intent of care, and the treatment received were recorded, and treatment compliance was assessed. Continuous and noncontinuous variables were described using median and proportions, respectively, and P < 0.05 was considered statistically significant. Results: A total of 1229 patients were included in the analysis, of which 87% were male and 90% belonged to Uttar Pradesh, a state in northern India. The predominant (91%) histological type was squamous cell carcinoma. Majority (81%) of the patients presented with disease in a locally advanced stage, and oral cavity was the most common sub-site (71%), followed by the oropharynx (9.7%) and the hypopharynx and larynx (10%). The treatment intent was curative in 62%, palliative in 31%, and supportive in 6% of the patients. Of patients receiving curative treatment, 12% received two to three cycles of neoadjuvant chemotherapy followed by surgery, 25% underwent upfront surgery followed by adjuvant chemo-radiation or radiation, 7% underwent surgery alone, and 11% received radical chemo-radiation. Among patients receiving treatment with palliative intent, 13% received oral metronomic chemotherapy and 13% received some form of intravenous chemotherapy. About 78% of the patients complied with their cancer-directed therapies, with male patients showing significantly better compliance than the female ones. Conclusion: This study reports the demographic profile and pattern of care of patients with HNCs from a newly developed tertiary care center in North India, and highlights the emergent need for a more dedicated cancer center in this region.